In memory of Ettore Grimaldi - Pietro Volta; Alcide Calderoni (Journal of Limnology, 2016)
Ettore Grimaldi (1934-2015) was one of the brightest and active ichthyologists in Italy. He was a man of great enthusiasm, boundless energy and great curiosity. He was a person with an open mind. He originally visited the Institute of Pallanza in June 1957 as a master student at the Faculty of Veterinary Medicine, University of Milan. He was formally called back by the Director Vittorio Tonolli, as a research assistant in 1962....